2009
DOI: 10.1099/vir.0.007054-0
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and growth kinetics of influenza viruses (H1N1 and H3N2) in the upper and lower airways of guinea pigs

Abstract: Recent investigations have shown that guinea pigs are important for the study of influenza A virus (IAV) transmission. However, very little is known about IAV replication and histopathology in the guinea pig respiratory tract. Here, we describe viral growth kinetics, target cells and histopathology in the nasosinus, trachea and lungs of IAV-infected guinea pigs. We found that guinea pigs infected with either A/Puerto Rico/8/34 (H1N1) or A/Hong Kong/8/68 (H3N2) developed a predominantly upper airway infection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
5
19
0
Order By: Relevance
“…Signs such as ruffled fur, listlessness, and anorexia are either absent or so subtle as to not be readily apparent in guinea pigs. Increased nasal mucus can be appreciated in infected animals (Tang and Chong, 2009; Bouvier and Lowen, 2010), but in our experience this sign is not consistently obvious and would be difficult to follow clinically, although it can be appreciated histopathologically (Tang and Chong, 2009). …”
Section: Animal Models Of Influenzamentioning
confidence: 67%
See 1 more Smart Citation
“…Signs such as ruffled fur, listlessness, and anorexia are either absent or so subtle as to not be readily apparent in guinea pigs. Increased nasal mucus can be appreciated in infected animals (Tang and Chong, 2009; Bouvier and Lowen, 2010), but in our experience this sign is not consistently obvious and would be difficult to follow clinically, although it can be appreciated histopathologically (Tang and Chong, 2009). …”
Section: Animal Models Of Influenzamentioning
confidence: 67%
“…Similarly, ambient temperature and humidity fluctuates seasonally in temperate climates, even in buildings with environmental control systems, and transmission efficiency may depend on the time of year. Finally, different inoculating doses of virus are often used (Nishiura et al, 2013), which has been shown to impact transmissibility or pathogenicity in ferrets and in guinea pigs (Tang and Chong, 2009; Herfst et al, 2012). …”
Section: The Influenza Virus Transmission Model In Ferrets and Guimentioning
confidence: 99%
“…Studies performed in guinea pigs showed that a neutrophilic infiltrate can be present in the very early stages of H1N1 infection causing acute bronchiolitis, bronchointerstitial pneumonia, and alveolitis. 13 However, other studies found that an outstanding feature in the early stage of infection is the absence of neutrophils in the infiltrate. 12 Even though it may be convenient to correlate the clinical findings with the histopathological findings, it remains unclear how the histopathological findings in H1N1 infection truly correlate with clinical comorbidities and bacterial coinfection because tissue sampling, patient susceptibilities, disease onset, and grading and interpretation of the histopathological findings are variable.…”
Section: H1n1 Autopsy Findingsmentioning
confidence: 98%
“…A key advantage of the model, compared to mice, is that guinea pigs are highly susceptible to infection with human strains (requiring no prior adaptation) (19)(20)(21). In addition, human influenza viruses show tissue tropism and kinetics of viral growth similar to those seen in uncomplicated influenza in humans (19,22,23). Importantly, human influenza virus strains transmit among guinea pigs by contact and respiratory droplet routes, whereas swine-adapted and some highly pathogenic avian influenza viruses transmit poorly and lowpathogenicity avian strains do not transmit (19)(20)(21)(24)(25)(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%
“…A disadvantage is that, to date, overt signs of disease have not been detected in influenza virus-infected guinea pigs. Nevertheless, rhinitis and bronchointerstitial pneumonia have been described (22,32). The utility of the guinea pig model is underlined by the fact that, since 2006, many additional labs have adopted it for the study of influenza virus transmission (33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%